Phylogeny and recombination of papaya begomoviruses in Northern and Central-East India - AARSHI SRIVASTAVA; VINEETA PANDEY; RAKESH KUMAR VERMA; AVINASH MARWAL; RAMWANT GUPTA; MUHAMMAD SHAFIQ SHAHID; R. K. GAUR (Nusantara Bioscience, 2025)
Abstract. Srivastava A, Pandey V, Verma RK, Marwal A, Gupta R, Shahid MS, Gaur RK. 2025. Phylogeny and recombination of papaya begomoviruses in Northern and Central-East India. Nusantara Bioscience 17: 298-312. Papaya plants exhibiting characteristic leaf curl symptoms were surveyed in 2022 across Uttar Pradesh, Delhi, and Chhattisgarh, India. Begomovirus infection was suspected based on symptomatology and confirmed in 11 of 47 collected samples using PCR with Begomovirus-specific primers. This study aimed to elucidate the diversity and distribution of begomoviruses infecting papaya in these regions. Full-length viral genomes were amplified through Rolling Circle Amplification (RCA), and associated alphasatellites and betasatellites were detected using PCR with universal primers. The amplified viral genomes (~2.7 kb), betasatellites (~1.4 kb), and alphasatellites (~1.3 kb) were cloned and sequenced. Sequence analysis revealed 94.57-99.46% nucleotide identity of DNA-A with known isolates of Papaya Leaf Curl Virus (PaLCuV), Cotton Leaf Curl Virus (CLCuV), Croton Yellow Vein Mosaic Virus (CYVMV), Tomato Leaf Curl New Delhi Virus (ToLCNDV), and Cotton Leaf Curl Multan Virus (CLCuMuV). The DNA-B component exhibited 98.33% identity with ToLCNDV. Ten betasatellites shared 86.81-99.71% identity with related species, whereas two alphasatellites showed approximately 98.5% identity with PaLCuA and PaLCVSA. One betasatellite (PL36) displayed 86.81% identity and was identified as a novel Papaya Leaf Curl Raipur Betasatellite (PaLCuRPRB). Furthermore, six PaLCuV isolates showing <91% identity was classified as new PaLCuV variants.